Mastering the Eight Paradoxes of Effective Leaders. - Mockaitis | How to Be Awesome at Your Job, Pete (linkedin.com, 2023)
Dr. Tim Elmore sheds light on the eight paradoxes the leaders of today must embrace to inspire and connect with their teams more effectively.